SCHOOL RESILIENCE ECOSYSTEM: MODEL KONTRA-RADIKALISME BERBASIS TRADISI PESANTREN MENGHADAPI CYBER-RADICALISM DI KALANGAN GEN-Z - Hadi Santoso; Ahmad Mukhlasin; Muslikhun Ibrohim Hizbulloh (Al-Iqro', 2026)
In 2024, the escalation of radicalism into the digital sphere, known as cyber-radicalism, poses a critical threat to Generation Z by exploiting social media algorithms to propagate exclusive ideologies. Amidst this digital vulnerability, pesantren-based madrasahs in Solo Raya demonstrate unique resilience mechanisms grounded in local wisdom. This study aims to analyze the construction of school resilience in countering radical narratives across three strategic institutions: MA Al-Muayyad Surakarta, MA Al-Manshur Klaten, and MA Al-Muttaqien Pancasila Sakti. Employing a qualitative method with a multi-site case study design, the research draws upon data from in-depth interviews, observations, and documentation. The findings reveal a comprehensive "School Resilience Ecosystem" supported by three core pillars: (1) Ideological Resilience, achieved through the internalization of the "Pancasila Sakti" doctrine and nationalist rituals to counter anti-state narratives; (2) Cultural Resilience, which utilizes arts such as Saman Dance and Batik to dismantle egoism and foster student inclusivity; and (3) Institutional Resilience, implemented through a non-violent pedagogical approach. The study concludes that integrating pesantren traditions (turats) provides an effective shield against global radicalism currents. Consequently, these findings imply a need for deradicalization policies to shift from a security-oriented approach toward a cultural immunization model.